γ-Aminobutyric acid, acting through γ-aminobutyric acid type A receptors, inhibits the biosynthesis of neurosteroids in the frog hypothalamus - Do-Rego, J. L. (The National Academy of Sciences, 2000)
Most of the actions of neurosteroids on the central nervous system are mediated through allosteric modulation of the γ-aminobutyric acid type A (GABA(A)) receptor, but a direct effect of GABA on the regulation of neurosteroid biosynthesis has never been investigated. In the present report, we have attempted to determine whether 3β-hydroxysteroid dehydrogenase (3β-HSD)-containing neurons, which secrete neurosteroids in the frog hypothalamus, also express the GABA(A) receptor, and we have investigated the effect of GABA on neurosteroid biosynthesis by frog hypothalamic explants. Double immunohistochemical labeling revealed that most 3β-HSD-positive neurons also contain GABA(A) receptor α(3) and β(2)/β(3) subunit-like immunoreactivities. Pulse-chase experiments showed that GABA inhibited in a dose-dependent manner the conversion of tritiated pregnenolone into radioactive steroids, including 17-hydroxy-pregnenolone, progesterone, 17-hydroxy-progesterone, dehydroepiandrosterone, and dihydrotestosterone. The effect of GABA on neurosteroid biosynthesis was mimicked by the GABA(A) receptor agonist muscimol but was not affected by the GABA(B) receptor agonist baclofen. The selective GABA(A) receptor antagonists bicuculline and SR95531 reversed the inhibitory effect of GABA on neurosteroid formation. The present results indicate that steroid-producing neurons of the frog hypothalamus express the GABA(A) receptor α(3) and β(2)/β(3) subunits. Our data also demonstrate that GABA, acting on GABA(A) receptors at the hypothalamic level, inhibits the activity of several key steroidogenic enzymes, including 3β-HSD and cytochrome P450(C17) (17α-hydroxylase).